2000
DOI: 10.1128/jb.182.3.589-598.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcription from Fusion Promoters Generated during Transposition of Transposon Tn 4652 Is Positively Affected by Integration Host Factor in Pseudomonas putida

Abstract: We have previously shown that both ends of the Tn3 family transposon Tn4652 contain integration host factor (IHF) binding sites and that IHF positively regulates expression of the Tn4652 transposase gene tnpA in Pseudomonas putida (R. Hõrak, and M. Kivisaar, J. Bacteriol. 180:2822-2829, 1998). Tn4652 can activate silent genes by creating fusion promoters during the transposition. The promoters are created as fusions between the ؊35 hexamer provided by the terminal inverted repeats of Tn4652 and the ؊10 hexamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Strain Generation-Introduction of the lacI Q /P tac -ihfAB mini-Tc transposon carried on the suicide plasmid pUTtetPF (24) into the chromosome of P. putida KT2440::dmpR-Tel was by conjugation from the E. coli donor host S17pir. Tellurite and tetracycline were used as counter selection for the donor and recipient parental strains, respectively.…”
mentioning
confidence: 99%
“…Strain Generation-Introduction of the lacI Q /P tac -ihfAB mini-Tc transposon carried on the suicide plasmid pUTtetPF (24) into the chromosome of P. putida KT2440::dmpR-Tel was by conjugation from the E. coli donor host S17pir. Tellurite and tetracycline were used as counter selection for the donor and recipient parental strains, respectively.…”
mentioning
confidence: 99%
“…This indicated that the fusion promoters are certainly stationary phase specific. Previously we have shown that transcription from the fusion promoters PRA1 and PLA1, containing sequences of either the right or left end of Tn4652, respectively, is modulated by IHF and that the positive effect of IHF becomes apparent in stationary-phase cells of P. putida (43). However, the fusion promoters cloned into the pKTLacZ reporter plasmid lacked functional IHF binding sites but were still expressed at an increased level in stationary-phase cells.…”
Section: Resultsmentioning
confidence: 98%
“…The S -independent increase in transcription became evident with all of the fusion promoters. Gel mobility shift experiments with Tn4652 ends and crude lysate of P. putida have revealed that in addition to IHF, some other proteins form specific complexes with the ends of Tn4652 (18,43). The amount of the protein-DNA complexes detected depends on the growth phase of the bacteria used for the preparation of cell extracts (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the efficient site-specific resolution of the Tn4651-mediated cointegrate required the two gene products, TnpS and TnpT, and the 2.4-kb region carrying tnpSres-tnpT was 48 kb apart from the tnpA gene (34). Although the cointegration step of Tn4651 has been extensively analyzed by Kivisaar's group (13,14,15,32), no detailed analysis of the resolution system has been carried out in more than a decade.…”
mentioning
confidence: 99%